2021
DOI: 10.1111/all.14769
|View full text |Cite
|
Sign up to set email alerts
|

Skewed inflammation is associated with aberrant interleukin‐37 signaling pathway in atopic dermatitis

Abstract: Background Atopic dermatitis (AD) is a severe global burden on physical, physiological, and mental health. The role of IL‐37, a fundamental inhibitor of immunity, in AD was herein explored. Method Serum levels of IL‐37 and T helper (Th) 2‐related inflammatory mediators were quantified in subjects with or without AD. The expression of IL‐37 receptors was determined by flow cytometry. Proteomics was employed to explore the serum protein profile and novel biomarkers. In vitro cell model, 3D‐keratinocytes mimickin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 64 publications
(113 reference statements)
2
21
2
Order By: Relevance
“…The poor anti-inflammatory effects observed in IL-37b+/− mice may be due to insufficient expression of IL-37b in the IL-37 heterozygous transgenic mice. In our previous study, AD patients showed a significant decrease in serum levels of IL-37 compared to healthy controls [ 29 ], in compliance with the significant reduction in IL-37 expression in skin lesions of AD patients, as revealed by other groups [ 30 , 31 ]. In parallel, IL-37 has been reported to be reduced in allergic or inflammatory diseases [ 32 , 33 , 34 ].…”
Section: Discussionsupporting
confidence: 74%
“…The poor anti-inflammatory effects observed in IL-37b+/− mice may be due to insufficient expression of IL-37b in the IL-37 heterozygous transgenic mice. In our previous study, AD patients showed a significant decrease in serum levels of IL-37 compared to healthy controls [ 29 ], in compliance with the significant reduction in IL-37 expression in skin lesions of AD patients, as revealed by other groups [ 30 , 31 ]. In parallel, IL-37 has been reported to be reduced in allergic or inflammatory diseases [ 32 , 33 , 34 ].…”
Section: Discussionsupporting
confidence: 74%
“…IL-37 levels in AD patients were significantly decreased, together with increased population of eosinophils (53). The serum concentration of involucrin, a keratinizing epithelia protein, in AD patients is significantly higher than that of HCs, which is related to the insufficiency of IL-37 (53). IL-37b suppresses the production of pro-inflammatory cytokines and chemokines in AD, increases autophagosome LC3B protein biogenesis and reduces the ubiquitinated protein p62 associated with autophagy through the activation of AMPK and the inhibition of mTOR (54).…”
Section: Regulation Of Eosinophil-and Mast Cell-mediated Inflammatory Responses By Il-37mentioning
confidence: 91%
“…The interaction between human eosinophils and dermal fibroblasts triggers allergic inflammation in atopic dermatitis (AD). IL-37 levels in AD patients were significantly decreased, together with increased population of eosinophils (53). The serum concentration of involucrin, a keratinizing epithelia protein, in AD patients is significantly higher than that of HCs, which is related to the insufficiency of IL-37 (53).…”
Section: Regulation Of Eosinophil-and Mast Cell-mediated Inflammatory Responses By Il-37mentioning
confidence: 92%
“…Gudjonsson et al reported evidence of altered Wnt signalling in the psoriatic skin 41 ; therefore, DKK1, a Wnt antagonist, can be a possible biomarker in inflammatory skin disease. The bioinformatics analysis of the proteome from the serum of AD patients demonstrated the altered landscape of immunological aberrations, and MANF was significantly increased in AD patients compared to HC 42 . These findings support the assumption that DKK1 and MANF are potential biomarkers despite the protein–gene gap.…”
Section: Discussionmentioning
confidence: 99%